Hansen solubility parameters (HSP) for prescreening formulation of solid lipid nanoparticles (SLN): in vitro testing of curcumin-loaded SLN in MCF-7 and BT-474 cell lines. (2nd January 2018) - Doktorovova, Slavomira; Souto, Eliana B.; Silva, Amélia M.
Abstract: Curcumin, a phenolic compound from turmeric rhizome ( Curcuma longa ), has many interesting pharmacological effects, but shows very low aqueous solubility. Consequently, several drug delivery systems based on polymeric and lipid raw materials have been proposed to increase its bioavailability. Solid lipid nanoparticles (SLN), consisting of solid lipid matrix and a surfactant layer can load poorly water-soluble drugs, such as curcumin, deliver them at defined rates and enhance their intracellular uptake. In the present work, we demonstrate that, despite the drug's affinity to lipids frequently used in SLN production, the curcumin amount loaded in most SLN formulations may be too low to exhibit anticancer properties. The predictive curcumin solubility in solid lipids has been thoroughly analyzed by Hansen solubility parameters, in parallel with the lipid-screening solubility tests for a range of selected lipids. We identified the most suitable lipid materials for curcumin-loaded SLN, producing physicochemically stable particles with high encapsulation efficiency (>90%). Loading capacity of curcumin in SLN allowed preventing the cellular damage caused by cationic SLN on MCF-7 and BT-474 cells but was not sufficient to exhibit drug's anticancer properties. But curcumin-loaded SLN exhibited antioxidant properties, substantiating the conclusions that curcumin's effect in cancer cells is highly dose dependent.